NOTARIAL ACT AS A PERFORMATIVE UTTERANCE - PIEPRZYCA, Piotr (Comparative Legilinguistics, 2016)
Performative utterances, or speech acts, shaping the extra-linguistic reality occur frequently in legal documents. One of such documents is a notarial act, drawn up by a notary and containing declarations of the parties which change the civil law relations. However, not all declarations in a notarial act are performative utterances: some of them describe the reality, without changing the civil law relations between the parties. A special case of a performative utterance is the signature of the parties, confirming the declarations written by a notary on behalf of the parties. This paper aims to illustrate the diversity of expressions which can be classified as performative utterances, and thus shows that the catalogue of these expressions is much broader than it is often presented in the linguistics literature.